Anti-inundation Measures for Underground Stations of Tokyo Metro. (2016) - Aoki, Yoji; Yoshizawa, Atsushi; Taminato, Tomoya
Abstract: Tokyo Metro Co., Ltd. (hereinafter, Tokyo Metro) comprises nine lines operating over 195.1km and 179 stations, and is used by 7.07 million passengers per day. Tokyo Metro operates on the belief that security equals safety plus service. In regard to safety, special effort is devoted toward countermeasures for natural disasters. In light of recent extreme weather events, countermeasures for heavy rains are particularly important. It was reported in the updated expectations for flood damage published in 2009 that metropolitan area's 17 lines and 97 stations and 147km of the tunnels will be completely submerged underwater. In response to expectations, we are developing and installing various waterproofing facilities at all tunnel entrances, ventilation openings, underground station entrances and other openings. Among these, underground station entrances are expected to suffer the most damage. Most Tokyo Metro station entrances are situated on sidewalks, there are many obvious spatial restrictions. In light of these restrictions, conventional waterproofing doors (hinged doors that apply positive pressure against floodwater pressure) cannot be used to improve all entrances, thus we have continued to develop counterpressure doors, hinged double doors, shutters, bi-fold doors and other types of waterproofing doors that fit the environments of individual entrances. In addition, few of the many buildings to which Tokyo Metro tunnels connect underground are prepared for the updated expectations for flood damage, meaning that Tokyo Metro must take action on its own property to prevent flood water inundation from such buildings. This means taking flood control measures in underground concourses with severe spatial limitations. Thus, we have developed counterpressure sliding doors capable of withstanding water pressure from flooding up to 15 m deep. This report describes updated expectations for floods, Tokyo Metro's improvement policy and descriptions of various types of underground waterproofing doors and the performance required of them.